Teaching and research of entrepreneurship in Canadian and Latin American business schools (1988)
In the 970’S a selected group of business managers and ownwers, and community leaders who had been involoved in the development of INCOLDA (Colombia Institute of Management) and of several other academic activities in Cali, decided to work toward the development of a new university in our city, which main field of knowledge would be: “Management and Business”.